KONSEP DASAR PENDIDIKAN ISLAM (Istilah Term Pendidikan Islam dalam al-Qur‟an) - ALI ANAS NASUTION (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2014)
In holy Quran, the phrase of Islamic educational is always using someterminologies in term likes  al-Tarbiyah, al-Ta‟lim  and  al-Ta‟dib. These terms have different meaning and different sense, although these terms areused in context of Islamic educational.  Based on these terms, the word of al-Tarbiyah  is always using, and got the popular place in circle of Islamic educational, so that,  the term of Islamic educational use “al-Tarbiyah al-Islamiyah”. Whereas the terms of al-Ta‟lim and al-Ta‟dim are used rarely.Nevertheless, these terms like as al-Tarbiyah, al-Ta‟lim and al-Ta‟dim have the same meaning.